Thefts of relics in Italy - Papasidero, Marco, author. Link
1 online resource.
Keywords: With the birth of the cult of the saints, their relics became valuables whose possession would guarantee prestige, protection, and spiritual benefits to a town, church, or monastery. For this reason-at first with the aim of preserving the bodies of newly-executed martyrs from destruction and later of increasing the power of a particular faction or community-, the relics began to be stolen, with numerous cases documented throughout Europe. At the same time, a rich hagiographic literature flourished to describe the contexts in which the thefts occurred and to demonstrate their authenticity. Justifications, legitimations, ordeals, and supernatural interventions are dotted throughout the stories of hagiographers over the centuries. This book seeks to reconstruct the cultural history of the theft of relics in the specific context of Italy, from Late Antiquity to the Central Middle Ages, availing itself of an interdisciplinary perspective.